The naturalistic theism of Henry Nelson Wieman (1884-1975) the creator of an American process theology - Rich, Charles Mark, 1925- (Lewiston, N.Y. : Edwin Mellen Press, 2012)
Henry Nelson Wieman was one of the most influential American religious figures of the late twentieth century. His work is examined here in relation to other notable thinkers such as Henri Bergson, William James, James Dewey, Alfred Whitehead, and Josiah Royce among others. He was also a mentor of Dr. Martin Luther King Jr. and his work set the stage for naturalistic theism. Wieman believed that creative religion constituted by self-giving individuals must always exist in relation to divine cosmic individuality. A radically individual nature of the process of change means that religion must enc
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Wieman, Henry Nelson, -- 1884-1975.; Theology -- History -- 20th century; Theology -- History -- 20th century; Wieman, Henry Nelson, 1884-1975.; RELIGION / Christian Theology / History; Electronic books